Felt Security in Daily Interactions as a Mediator of the Effect of Attachment on Relationship Satisfaction1. Issue 2 (March 2015) - Sadikaj, Gentiana; Moskowitz, D. S.; Zuroff, David C.
Abstract: This study examined how felt security in interpersonal situations with one's romantic partner mediated the effect of global (dispositional) attachment on relationship satisfaction. Felt security was measured using an event‐contingent recording (ECR) methodology with a sample of 93 cohabiting couples who reported their social interactions with each other during a 20‐day period. Global attachment was measured at the beginning of the ECR procedure. Relationship satisfaction was measured at the end of the ECR procedure (T1) and approximately 7 months after the ECR procedure (T2). Results confirmed the established links between attachment and relationship satisfaction such that higher attachment avoidance and attachment anxiety were associated with decline in satisfaction over time. Results also indicated that attachment avoidance but not attachment anxiety was negatively related to felt security, both within‐partner and across‐partners. As expected, lower felt security exerted a negative effect on relationship satisfaction at T1 and T2, and partly mediated the effect of attachment avoidance on relationship satisfaction at T1 and T2, both within‐partner and across‐partners. Partners' gender emerged as a moderator of these results. Findings suggest higher attachment avoidance leads to less felt security in daily social interactions, which leads to less satisfaction with the romantic relationship. Copyright © 2015 European Association of Personality Psychology